Grand strategy and military alliances - Mansoor, Peter R., 1960-; Murray, Williamson (Cambridge : Cambridge University Press, 2016)
Alliances have shaped grand strategy and warfare since the dawn of civilization. Indeed, it is doubtful that the United States of America would have gained its independence without its Revolutionary War alliance with France. Such alliances may prove even more important to international security in the twenty-first century. Economic and financial difficulties alone will ensure that policy makers attempt to spread the burden of securing vital interests onto other nations through alliances, both formal organizations such as NATO and informal alliances of convenience as developed to wage the Gulf War in 1991. A team of leading historians examine the problems inherent in alliance politics and relationships in the framework of grand strategy through the lens of history. Aimed at not just the military aspects of alliances, the book uncovers the myriad factors that have made such coalitions succeed or fail in the past.
Title from publisher's bibliographic system (viewed on 05 Feb 2016).
Keywords: Alliances -- History -- Case studies; Strategy -- History -- Case studies